New and little known Limacodidae (Lepidoptera) from Xizang, China - Pan, Zhaohui; Wu, Chunsheng (Zootaxa, 2015)
Five new and little known species of Limacodidae are reported from Xizang, China. Among them, Pseudohampsonella bayizhena Wu & Pan, sp. nov. and Squamosa monosa Wu & Pan, sp. nov. are described as new, Pseudocaissa Solovyev & Witt and P. marvelosa (Yoshimoto) are newly recorded in China, and Miresa urga Hering and Scopelodes kwangtungensis Hering are reported for the first time in Xizang. The female genitalia are described for the first time in the genus Squamosa Bethune-Baker. Photographs of moths and the genitalia of new species and newly recorded species are given. A list of the Limacodidae known from Xizang, China is also included.